The zinc finger proteins ZC3H20 and ZC3H21 stabilise mRNAs encoding membrane proteins and mitochondrial proteins in insect‐form Trypanosoma brucei - Liu, Bin; Marucha, Kevin; Clayton, Christine (Molecular microbiology, 2020)
African trypanosomes are parasites that can grow in the blood of mammals, as